2018
DOI: 10.20546/ijcrar.2018.609.006
|View full text |Cite
|
Sign up to set email alerts
|

Response of Soybean (Glycine max (L) Merrill) to Plant Population and NP Fertilizer in Kersa Woreda of Jimma Zone, South Western Ethiopia

Abstract: Article Info Declining soil fertility status and poor agronomic practices, including minimum use of inorganic fertilizers and inappropriate plant population are the major reasons for low productivity of soybean. A field experiment was carried out to determine the response of soybean to plant population and NP fertilizer in Kersa woreda of Jimma zone, south western Ethiopia during the 2015/2016 cropping season. Four levels of NP fertilizer (23/23, 23/46, 46/46 and 69/69 kg/ha) and plant population (166667, 2000… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 17 publications
0
0
1
Order By: Relevance
“…This study was supported by previous findings reported by Daniel et al(2014) who recorded a highly significant variation among varieties of haricot bean plants that were evaluated for harvest index. In contrast to this result, Habtamu et al (2018) reported that the main effect of plant population did not show significant variations on harvest index of soybean cultivar. And, Sobko et al (2019) reported that the main effect of inter row spacing on harvest index was stable characteristic within a cultivar and was not affected by planting density of soybean cultivar.…”
Section: Hundred Grains Weightcontrasting
confidence: 88%
“…This study was supported by previous findings reported by Daniel et al(2014) who recorded a highly significant variation among varieties of haricot bean plants that were evaluated for harvest index. In contrast to this result, Habtamu et al (2018) reported that the main effect of plant population did not show significant variations on harvest index of soybean cultivar. And, Sobko et al (2019) reported that the main effect of inter row spacing on harvest index was stable characteristic within a cultivar and was not affected by planting density of soybean cultivar.…”
Section: Hundred Grains Weightcontrasting
confidence: 88%